Associação e fatores de risco para a hipertensão arterial sistêmica em pessoa vivendo com HIV, em comparação com população não infectada pelo HIV: uma revisão sistemática com meta-análise - Gomes, Mariene Garcia (2025)
Introduction Research on the prevalence of hypertension among People living with HIV/AIDS (PLWHA) has yielded conflicting results. The association and risk factors for this condition, when comparing PLWHA to non-infected individuals, remain inconclusive and may be related to traditional risk factors or HIV-specific characteristics. Objective: To evaluate the association and risk factors for hypertension in PLWHA compared to non-infected individuals. Methods: A systematic review with meta-analysis of observational studies (cross-sectional, cohort, and case-control) was conducted. Searches were performed in four databases (PubMed, Embase, Web of Science, and Global Index Medicus), supplemented by manual searches of reference lists from included studies. Retrieved results were imported into the Covidence® software, where duplicates were removed, and study selection and data extraction were conducted. Eligible participants were those aged ≥18 years with a medical diagnosis of hypertension, self-reported hypertension diagnosis, use of antihypertensive medication, or studies using electronic health records to classify participants with hypertension. Studies conducted with children and adolescents under 18 years old, pregnant women, non-systemic hypertension, and other study designs were excluded. The methodological quality of the included articles was assessed using the Newcastle-Ottawa Scale for cohort and case-control studies and the Joanna Briggs Institute Checklist for Analytical Cross-Sectional Studies for cross-sectional studies. Outcomes evaluated included systolic and diastolic blood pressure by HIV status, the association between HIV status and hypertension, and risk factors for hypertension. Continuous outcome data were summarized using the mean difference (MD) as the effect measure, based on a random-effects model. Binary outcomes were analyzed using the relative risk (RR) and 95% confidence interval (CI). Heterogeneity was quantified using Cochran's Q test and Higgins' I² test. Publication bias was assessed through funnel plots and Egger’s statistical test. Results: 24 studies were included, though only cross-sectional studies (n = 21) were analyzed in the meta-analysis. Five studies were of low methodological quality, nine of moderate quality, and ten of high quality. PLWHA had a 9% lower risk of hypertension compared to non-infected individuals, but this difference was not statistically significant (RR 0.91, 95% CI: 0.76–1.09). Considerable heterogeneity was observed (I² = 98.4%), and the funnel plot revealed an asymmetric distribution, confirmed by Egger’s test. PLWHA tended to have significantly lower systolic blood pressure than non-infected individuals (MD: -3.67, 95% CI: -6.70; -0.64). Regarding diastolic blood pressure, although PLWHA showed lower values than non-infected individuals, the difference was not statistically significant (MD: -0.21, 95% CI: -2.38–1.96). Additionally, women (RR 0.46, 95% CI: 0.27–0.79) and overweight HIV-infected participants (RR 0.74, 95% CI: 0.56–0.98) had a significantly lower risk of hypertension compared to non-infected individuals. Conclusion: The results showed that PLWHA had lower mean differences in systolic and diastolic blood pressure and risk in the association between HIV status and hypertension. However, interpretations require caution due to the low to moderate methodological quality and high heterogeneity.